2021
DOI: 10.3389/fimmu.2021.746151
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Inflammation and Metabolic Reprogramming of Macrophages in Diabetes and Obesity: The Importance of Metabolites

Abstract: Diabetes mellitus type II and obesity are two important causes of death in modern society. They are characterized by low-grade chronic inflammation and metabolic dysfunction (meta-inflammation), which is observed in all tissues involved in energy homeostasis. A substantial body of evidence has established an important role for macrophages in these tissues during the development of diabetes mellitus type II and obesity. Macrophages can activate into specialized subsets by cues from their microenvironment to han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 129 publications
0
66
0
1
Order By: Relevance
“…Previous studies have indicated that gut microbiota dysbiosis is one of the reasons for obesity and related disorders, and fecal microbial transplantation (FMT) is considered a potential source of novel therapeutics (Napolitano and Covasa, 2020;He et al, 2021;Voland et al, 2021). FMT from the obesity-associated human gut microbiota to mice can induce vascular dysfunction and glucose intolerance, and FMT from lean donors to patients with obesity can promote metabolic benefits (Mocanu et al, 2021;Russo et al, 2021). Recent studies over the past decade have revealed that many environmental factors, including diet, antibiotic exposure, energy intake and exercise, can dramatically influence the gut microbiota (Du et al, 2021;Giordan et al, 2021;Shi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated that gut microbiota dysbiosis is one of the reasons for obesity and related disorders, and fecal microbial transplantation (FMT) is considered a potential source of novel therapeutics (Napolitano and Covasa, 2020;He et al, 2021;Voland et al, 2021). FMT from the obesity-associated human gut microbiota to mice can induce vascular dysfunction and glucose intolerance, and FMT from lean donors to patients with obesity can promote metabolic benefits (Mocanu et al, 2021;Russo et al, 2021). Recent studies over the past decade have revealed that many environmental factors, including diet, antibiotic exposure, energy intake and exercise, can dramatically influence the gut microbiota (Du et al, 2021;Giordan et al, 2021;Shi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…LPS can recognize toll-like receptor 4 (TLR4) and then activate NF-κB signaling, which promotes the secretion of MCP1 and recruitment of proinflammatory macrophages (Catrysse and van Loo, 2017). Furthermore, obesity leads to release of proinflammatory mediators such as IL-1β, IL-6 and MCP-1, and then causes circulating monocytes recruitment and macrophages accumulation in adipose tissue (Russo et al, 2021). Our results showed that PDX treatment reduced serum LPS and IL6 levels and significantly inhibited NF-κB signaling in the epididymal adipose tissue of HFD-fed mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classically activated, proinflammatory M1 macrophages depend to a large extent on glycolysis and produce lactate as the tricarboxylic acid cycle is blocked at two steps. Alternatively activated M2 macrophages prefer β-oxidation and oxidative phosphorylation to synthesize ATP (for an excellent review, see [ 61 ]). It is well established that continuous and excessive inflammatory stimuli, e.g., in various inflammatory and metabolic diseases, including T2DM, lead to macrophage activation.…”
Section: M1/m2 Macrophage Polarizationmentioning
confidence: 99%
“…Many factors favour the occurrence of symptomatic COVID-19, especially aging, diabetes, heart disease or obesity [52][53][54][55]. All these clinical conditions are associated with microglial inflammation (microglial type 1 status) [56,57].…”
Section: Primo-infection Of Covid-19 and Microgliamentioning
confidence: 99%